6개월간의 저염식이 여자 대학생의 짠맛에 대한 인지와 기호, 혈압 및 뇨 나트륨 배설량에 미친 영향 - 장순옥(Chang Soon-Ok) (Hanʼguk yongyang hakhoe chi, 2010)
The study aim was to examine the effect of sensory responses of subjects after 6-month dietary sodium reduction with the aid of nutritional education. Fourteen female college students voluntarily restricted their sodium intake for 6 months, during which time they received nutritional education on the low sodium diet. As a control group, 10 students, whose anthropometric measurement, sodium intake behavior, and blood pressure were not different from those of the experimental group, were maintained on a normal diet. For the sensory responses of subjects, the salt taste perception and pleasantness for graded (0.15-1.3%) NaCl solutions were measured by a 9-point hedonic scale. The optimum sodium concentration, urinary sodium excretion, and blood pressure were measured. All the measurements were done at the beginning and end of the experiment. The sensory evaluation revealed an absence of any difference between the two groups in salt taste perception and pleasantness responses at the beginning. After 6-month adaptation, the experimental group subjects showed higher responses to low NaCl solution (0.15, 0.3, 0.5%) in salt taste perception and pleasantness evaluation while the control group subjects exhibited the opposite response. The optimum sodium concentration was reduced from 105.6 mmol to 80.7 mmol (p = 0.015) and the urinary sodium excretion was also reduced from 1,398 mg to 906 mg (p = 0.041) only in the experimental group. Systolic blood pressure was significantly reduced in the experimental group, although there was no correlation between the urinary sodium excretion and blood pressure. The optimum sodium concentration was negatively correlated with the urinary sodium excretion (r = 0.418, p = 0.053), indicating that adaptation to low sodium diet can reduce sodium intake. Further study on the individual responses of subjects on a low sodium diet by periodical evaluation may provide useful data for setting the duration needed to stabilize a lowered appetite for sodium. 본 연구는 여자대학생을 대상으로 장기간의 자율적 저염식 실시가 짠 맛에 대한 인지와 기호에 영향을 미쳐 나트륨 섭취나 혈압에 변화를 가져 올 수 있는지를 조사하고자 실시되었다. 14명의 실험군 대상자들은 나트륨 관련 영양교육과 정보를 제공받아 저염식을 하도록 지시 받았고 10명의 대상자는 평상시의 식생활을 유지하도록 하였다. 짠 맛의 인지와 기호는 9점 척도의 관능검사로 평가하였고 뇨 나트륨 배설량과 최적 염미 나트륨 정량 분석하였으며 혈압을 측정하였다. 주요 연구 결과는 아래와 같다. 1) 연구 시작시의 실험군과 대조군은 나트륨 관련 식행동, 신체 계측치, 혈압, 24시간 회상법에 의한 나트륨 섭취량, 6단계의 염분용액에 대한 짠 맛 인지나 기호에서 차이가 없었다. 2) 6개월의 저염식 실시 후 실험군 대상자들은 0.5% 이하 염분 용액에서 짠 맛 인지도가 높아졌고 대조군은 낮아져 저염식 실시로 낮은 농도의 염분에 적응한 듯하나 연구시작과 종료시의 paired t-test에서 통계적 유의성은 없었다. 기호도는 시작 시에는 두 군 모두 0.5% 염분 용액을 가장 선호했고 연구 종료시 대조군은 0.75%와 0.5% 염분 용액에 비슷한 기호도를 보인 반면 실험군은 0.5%, 그 다음으로 0.3% 용액에 높은 기호도를 보였으나 그 변화가 유의적 수준은 아니었다. 3) 최적 염미 나트륨 농도는 실험군에서 105.6 mmol에서 저염식 적응 후 80.7 mmol로 유의적 (p = 0.015) 감소를 보였고 대조군은 변화가 없었다. 뇨 나트륨 배설량은 대조군은 연구 시작과 종료시 차이가 없었고 실험군은 연구 종료시 1,398 mg에서 906 mg으로 유의적 감소를 하였다. 4) 수축기 혈압은 실험군 대상자에서 111 mmHg에서 106 mmHg로 유의적으로 감소하였고 이완기 혈압은 대조군, 실험군 모두에서 유의적으로 감소하였다. 혈압과 뇨 나트륨 배설량은 상관관계를 나타내지 않았다. 5) 최적 염미 나트륨 농도와 뇨 나트륨 배설량은 양의 상관관계 (r = 0.418)을 보여 짠맛에 대한 기호가 나트륨 섭취량에 영향을 미친 것으로 보인다. 최적 염미 나트륨 농도와 뇨 나트륨 배설량은 0.5% 이하의 낮은 염분 용액에 대한 짠 맛의 인지와는 음의 상관관계 (r = -0.338~-0.399)를 보여 저염식을 하는 대상자는 낮은 염도에도 잘 반응함을 보여 주었다. 본 연구의 대상자들은 6개월 간의 실험 경과 후 최적 염미도와 뇨 중 나트륨 배설량에서는 대조군과 실험군의 차이가 분명하였고 관능검사 결과는 0.5% 이하의 저염 농도에 실험군 대상자들이 짠 맛 인지와 기호도가 유의적이지는 않으나 향상하였다. 혈압은 수축기 혈압이 실험군에서만 유의적으로 감소하여 전반적으로 6개월 간의 저염식 적응이 유효한 듯하다. 그러나 본 연구결과만으로는 저염식에 적응해 가는 변화과정을 알 수 없고 분석 자료의 표준편차로 보아 개인차 커 일부 비적응자가 있었음을 알 수 있다. 앞으로 저염 적응 기간 중 개인별 반응과 함께 여러 시점에서의 관찰이 필요하다고 본다.